Visual Interpretation of the ANTARAKATA MSME Logo in Building Brand Identity - Vadisya Dhiaul Aulia; Arif Fiyanto (Gorga : Jurnal Seni Rupa, 2025)
A logo is an essential element in building the visual identity of MSMEs, as it serves not only as an identifier but also as a representation of the values, vision, and mission of a business. However, the current phenomenon shows that most MSMEs still treat logos merely as decorative symbols without understanding their strategic power in shaping brand image and competitiveness. This condition creates a gap between the strategic potential of logos and their practical use in the field. On the other hand, previous studies have largely highlighted the role of logos in strengthening brand image, yet specific research discussing the visual interpretation of MSME logos based on Gestalt theory and semiotics remains limited. In fact, this approach is crucial to understanding how visual elements such as typography, color, and form can be perceived holistically by consumers. This study fills that gap by analyzing the logo of MSME ANTARAKATA through a semiotic and Gestalt theory perspective as a state-of-the-art approach in design analysis. The research focuses on three main elements: capital sans-serif typography that represents a modern and professional impression, a yellow-brown color combination that builds harmony between creativity and trust, and a simple wordmark form that strengthens the clarity of brand identity. The analysis shows that the ANTARAKATA logo successfully creates consistent visual unity, is easy to recognize, and builds emotional attachment with consumers. Thus, this study emphasizes the importance of logo design based on visual theory as a branding strategy for MSMEs in facing increasingly intense business competition.